Labour market participation and access to internet during Covid-19 lockdown: Case of South Africa - Mariti, Relebohile (School of Economics, 2024)
The labour markets have become digitalised with the rise of the internet. As economies undergo industrial revolutions, various aspects of the labour market have been greatly impacted by internet use and access to information and communication technologies worldwide. Among others, the internet has affected labour market transparency, job search and matching. In addition, the recent pandemic (COVID-19) has also highlighted the crucial role that information and communication technologies as well as internet access play in the labour market. In this study, we investigate how internet access at home influences labour market attachment at the extensive margin in South Africa. Using the data from the 2020 and 2021 General Household Surveys administered by Statistics South Africa, and three identifications strategies (instrumental variable strategy, panel data methods and propensity score matching), the study finds a desirable effect of household internet connection on both the probability of being employed and the likelihood of being economically active. Moreover, the estimation results from the supplemental analysis indicate that household internet connection has a positive influence on likelihood of being employed for males and there is no sufficient evidence to suggest a corresponding effect on labour market attachment of females. Unless otherwise stated, the strict definition of unemployment is used to measure labour force participation in this study. The main findings of this study suggest that internet diffusion in recent years enabled productive South Africans to participate in the labour market. Hence policies aimed at redressing digital inequality by promoting awareness of benefits of using the internet and how to use the internet as well as subsidising data to enhance the adoption and use of internet at home are necessary to stimulate labour supply.